Thymic malignancies: next-generation sequencing as a tool to select patients for targeted therapies and immunotherapies? - Girard, Nicolas (Mediastinum; Vol 3 (September 2019): Mediastinum, 2019)
The management of thymic malignancies is based on multidisciplinary discussion. Systemic agents may be administered as an exclusive treatment if local treatment is not achievable. Novel and innovative agents are used based on the results of next-generation sequencing that may report the activation of targetable signaling pathways both in thymomas and thymic carcinomas. Phase II trials reported the antitumor activity of PI3K/mTOR inhibitors, CDK inhibitors, and antiangiogenic agents in advanced, refractory, or metastatic thymic epithelial tumors. The use of immune checkpoint inhibitors is challenging given the frequent association of those tumors with auto-immune disorders. Meanwhile, a better understanding of systemic treatment sequences in a real-life setting is mandatory to analyze the actual indication of each agent, define the potential biomarkers for the selection of patients, and develop individualized decision-making to optimize the survival of patients.